Identification of the transcriptional biomarkers panel linked to pathological remodelling of the eye tissues in various HD mouse models. - Mazur-Michaek,I; Ruciski,M; Sowiski,M; Pietras,P; Leniczak-Staszak,M; Szaflarski,W; Isalan,M; Mielcarek,ML (Cells, 2022)
Ocular abnormalities are becoming associated with a spectrum of pathological events in various neurodegenerative diseases. Huntington’s disease (HD) is just such an example of a fatal neurological disorder, where mutated genes (CAG trinucleotide expansions in the Huntingtin gene) have widespread expression, leading to the production of mutant Huntingtin (mHTT) protein. It is well known that mutant HTT protein is prone to form toxic aggregates, which are a typical pathological feature, along with global transcriptome alterations. In this study, we employed well-established quantitative methods like Affymetrix arrays and quantitative PCR (qPCR) to identify a set of transcriptional biomarkers that will track HD progression in three well-established mouse models: R6/2, R6/1 and HdhQ150. Our array analysis revealed significantly deregulated networks that are related to visual processes and muscle contractions. Furthermore, our targeted quantitative analysis identified a panel of biomarkers with some being dysregulated even at the presymptomatic stage of the disease, e.g. Opn1mw, Opn1sw and Pfkfb2. Some of the deregulated genes identified in this study have been linked to other genetic ocular disorders like: GNAT2, a source of achromatopasia; and REEP6, linked to Retinitis pigmentosa. It may thus be a useful platform for preclinical evaluations of therapeutic interventions.